Employees or Consumers? The role of competing identities in individuals' evaluations of corporate reputation. Issue 6 (21st June 2018) - Puncheva-Michelotti, Petya; Vocino, Andrea; Michelotti, Marco; Gahan, Peter
Abstract : Purpose: The purpose of this paper is to investigate the manners in which the employee and consumer identities interact to shape individuals perceptions of corporate reputations in well-established market economies (Australia and Italy) and transition countries (Bulgaria and Russia). Design/methodology/approach: The study utilises a within-subjects repeated measures design. The data were collected from 892 subjects in Australia, Italy, Bulgaria and Russia. The hypotheses were tested using structural equation modelling. Findings: In established market economies, individuals tend to have very distinct identities as employees or consumers, and make different evaluations of corporate reputations depending on the chosen identity. In contrast, in transition countries, the consumer identity prevails over the employee identity and therefore job seekers tend to "follow" their consumer values in forming value judgements of companies. Originality/value: The study makes two key contributions to current debates in employer branding and stakeholder management research. First, it contributes to theory and practice in employer branding by developing and testing a model of the interaction between consumer and employee identities in defining individuals' perceptions of corporate reputations. Second, it contributes to stakeholder theory by investigating consumption and job-search from an integrated perspective rather than as separate and unrelated processes.